How to foster green product innovation in an inert sector - Patrick Ilg (Journal of Innovation & Knowledge (JIK), 2019)
Green product innovations offer a large number of compelling benefits to different stakeholders throughout their life cycle (raw material extraction, production, use and maintenance, end of life). However, in inert sectors such as the construction industry, the development of green products is still too slow to meet future needs. To push green innovation, this article investigates the application of a virtuous circle in the construction industry. Additionally, the potential of green product innovations to generate and sustain economic growth is analyzed. Finally, barriers and practical implications for a green construction industry are presented. The qualitative study is based on a literature review, 25 expert interviews, and three case studies of green leaders. Results indicate that a virtuous circle is possible and has the potential to change the construction industry. Moreover, green product innovations strengthen efficiency and core competences. However, high perceived initial costs, outdated accounting methods, and the complexity of construction projects are identified as main barriers to implementation. These barriers can be counteracted by 1) increased awareness among consumers and institutional investors, 2) collaboration and knowledge transfer between stakeholders, and 3) a pull-effect of green leaders who communicate the financial and environmental benefits of green projects. The results support the resource dependence theory and demonstrate the relevance of the external environment on companies.
Keywords: L1; L2; O3; Q2; Q5; R3; 650; Green product development; Green product innovation; Green real estate; Resource dependence theory; Virtuous circle